2022
DOI: 10.3389/fbuil.2022.1026225
|View full text |Cite
|
Sign up to set email alerts
|

Automatic assessment of roofs conditions using artificial intelligence (AI) and unmanned aerial vehicles (UAVs)

Abstract: Building roof inspections must be performed regularly to ensure repairs and replacements are done promptly. These inspections get overlooked on sloped roofs due to the inefficiency of manual inspections and the difficulty of accessing sloped roofs. Walking a roof to inspect each tile is time-consuming, and as the roof slope increases, this difficulty increases the time needed for an inspection. Moreover, there is an intrinsic safety risk involved. Falls from roofs tend to cause severe and expensive injuries. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Ahmet Bahaddin Ersoz et al [39] processed a UAV-based pavement crack recognition system by processing UAV-based images for support vector machine (SVM) model training. Ammar Alzarrad et al [40] demonstrated the effectiveness of combining AI and UAVs by combining high-resolution imagery with deep learning to detect disease on roofs. Long Ngo Hoang, T et al [41] presented a methodology based on the mask regions with a convolutional neural network model, which was coupled with the new object detection framework Detectron2 to train a model that utilizes roadway imagery acquired from an unmanned aerial system (UAS).…”
Section: Aircraft-based Evaluation Methodsmentioning
confidence: 99%
“…Ahmet Bahaddin Ersoz et al [39] processed a UAV-based pavement crack recognition system by processing UAV-based images for support vector machine (SVM) model training. Ammar Alzarrad et al [40] demonstrated the effectiveness of combining AI and UAVs by combining high-resolution imagery with deep learning to detect disease on roofs. Long Ngo Hoang, T et al [41] presented a methodology based on the mask regions with a convolutional neural network model, which was coupled with the new object detection framework Detectron2 to train a model that utilizes roadway imagery acquired from an unmanned aerial system (UAS).…”
Section: Aircraft-based Evaluation Methodsmentioning
confidence: 99%
“…Utilizing infrared sensors also highlights areas of moisture intrusion within wall systems signaled by temperature differentials [119]. A study by Alzarrad et al [159] presented a promising approach to automating sloped roof inspections using UAVs and deep learning. It highlighted the significance of such technology in enhancing efficiency, reducing safety risks, and providing accurate assessments of roof conditions.…”
Section: B Building Envelope Performancementioning
confidence: 99%